Analisis Perencanaan Pengendalian Persediaan untuk Meminimalkan Overstock Paperbag (Studi Kasus: UD. Lestari Jaya Selalu) - Amalia Rizka Febriyanti; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. Lestari Jaya Selalu is a company engaged in paper bag production and experiences overstock problems due to the amount of finished goods inventory exceeding warehouse capacity. This condition causes increased storage costs and the risk of company losses. This study aims to determine the optimal method for planning and controlling raw material requirements and analyzing losses due to overstock. The method used is Material Requirement Planning (MRP) with the lot sizing technique Lot-for-Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). Demand forecasting is carried out using the Linear Trend Line Model and Exponential Smoothing with Trend methods. The results show that the Linear Trend Line Model has the lowest forecasting error rate. In addition, the LFL method produces the lowest total inventory cost of Rp20,748,000 for paper bag products measuring 25x30 and 20x25. The LFL method is considered effective in adjusting raw material requirements and reducing the risk of overstock, thereby increasing the company's operational efficiency.